Peran Mahasiswa Kuliah Praktek dan Pengabdian Kepada Masyarakat (KPPM) di Desa Pohan Tonga Kec. Siborong-borong - Kalep Ompusunggu; Glory Sibuea; Deni Cardok Tarigan (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
One type of student service needed by IAKN Tarutung is the Community Service and Practice (KPPM), which takes place in the sixth semester and lasts for three months. Through various community experiences and social activities that involve cooperation between students, the community, and the government, this program aims to meet basic needs and improve the welfare and tranquility of the community in Pohan Tonga Village, Siborongborong District. The two main phases of the research methodology are observation at the village head's office and the implementation of health program activities for the elderly every Wednesday. This activity lasts for 120 minutes and is scheduled once a month in the third week. Activities may include worship, counseling, community service, and physical activities. The community is becoming closer and supporting one another through events facilitated by KPPM such as village clean-ups, community service, and other social gatherings. This creates a peaceful village atmosphere and enhances relationships among residents. Village development projects are planned, implemented, and evaluated with community participation encouraged by KPPM. The community actively participates rather than just watching, fostering a sense of pride in the developmental outcomes. The conclusion of this activity is that KPPM investigates and utilizes the existing potential of Pohan Tonga village, including its human and natural resources. This potential can be a key asset for village development with proper management.